Sleep recovery ameliorates submandibular salivary gland inflammation associated with paradoxical sleep deprivation in male Wistar rats - Jude Ijuo Abeje; Shehu-Tijani T. Shittu; Olayinka Olawale Asafa; Bimpe Bolarinwa; Taye J. Lasisi (Journal of Applied Oral Science)
Abstract Submandibular salivary gland inflammation has been suggested as one of the mechanisms underlying impaired salivary secretion associated with sleep deprivation (SD). However, whether the salivary inflammatory response occurs to the same extent in paradoxical sleep deprivation with or without sleep recovery remains unknown. Objective: This study evaluated the extent to which inflammation influences salivary impairments associated with paradoxical sleep deprivation with or without sleep recovery. Methodology: Male Wistar rats were randomly assigned into three groups as control, partial SD (PSD) with sleep recovery for four hours a day and total SD (TSD). Paradoxical SD was carried out for seven days in the SD groups, after which saliva, blood, and submandibular gland samples were taken. Levels of interleukin-6 (IL-6), tumour necrosis factor-alpha (TNF-α), and nitrite were determined in saliva, serum, and the submandibular salivary gland. Leucocyte count and neutrophil-lymphocyte ratio were determined in all groups. One-way ANOVA and the Tukey's post hoc tests were used for data analysis. P-values < 0.05 were considered statistically significant. Results: Levels of TNF-α, IL-6, and nitrite in the submandibular salivary glands were significantly higher in the TSD groups (p=0.04,p<0.001, p=0.03, respectively) than in the control. Saliva level of TNF-α was higher in the PSD and TSD groups (p=0.003 and p=0.01 respectively) than in the control. Neutrophil-lymphocyte ratio was significantly higher in both PSD and TSD groups than in the control (p<0.01 for both). Conclusion: While total SD produced higher inflammatory response in the submandibular salivary gland, four-hour sleep recovery ameliorated this impact. This finding suggests that sleep recovery is crucial to improve inflammatory salivary gland dysfunction induced by sleep deprivation.